Leseng Community Political Participation in the 2020 Regional Elections Based on Education Level - Kariyani, Leni Nurul (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2024)
Leseng Village is one of the villages with the third highest level of participation in the Moyo Hulu sub-district, with a total vote reaching 89.65%. In addition, the level of education in Leseng village is also a village with quite advanced education. Education and political participation are two related things. The purpose of this study was to determine the extent of the influence of education level on people's political participation in the 2020 Sumbawa regional elections and to find out other factors that influence people's political participation in Leseng Village in the 2020 Sumbawa regional elections. This research uses quantitative methods with data collection techniques using a questionnaire (questionnaire). From the research that has been done, there is a significant influence of education on political participation. Then there are several other factors that influence the political participation of the Leseng village community, namely: self-factors, environmental/family factors, stimulation/lure factors, social sensitivity factors, and approach factors taken by pason/timses with the community.